PENGARUH PUPUK HAYATI ENDOMIKORIZA ASAL AKAR MERANTI (Shorea sp) TERHADAP PRODUKSI TANAMAN KANGKUNG (Ipomea reptans) DAN BAYAM (Amaranthus sp) - Huwae, Linda Naomi; Matinahoru, Johan Markus; Siahaya, Ludia (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aims to determine the impact of endomycorrhizal biofertilizer from meranti roots (Shorea sp) on the production of kale (Ipomea reptans) and spinach (Amaranthus sp) and analyze its effectiveness on production. Meranti root samples as raw materials for making biofertilizer were taken from Honitetu Village, Inamosol District, West Seram Regency and then research was conducted in Lateri Village, Baguala District, Ambon City. This research took place from February to March 2025. The method used was RAL (Completely Randomized Design) consisting of 2 treatments and 3 replications. The first treatment is fertilizer, which consists of 4 levels, namely A0 (No fertilizer), A1 (NPK Fertilizer), A2 (Endomycorrhizal Biofertilizer, A3 (Endomycorrhizal Biofertilizer + NPK Fertilizer). The second treatment is the type of plant consisting of 2 levels, namely B1 (Kangkung) and B2 (Spinach). The parameters observed are plant height (cm) and number of leaves (strands). The results of the study showed that the interaction between endomycorrhizal biofertilizer and plant types had a significant effect and provided the highest value on the production of kale plants compared to spinach plants.